HUBUNGAN ANTARA ETOS KERJA, MOTIVASI, SIKAP INOVATIF DAN PRODUKTIVITAS USAHATANI (Studi Kasus Pada Usahatani Padi Sawah di Kecamatan Tumpaan Kabupaten Minahasa Selatan) - Vicky R. B. Moniaga (AGRI-SOSIOEKONOMI, 2012)
This study aims to (a) describe these three psychological factors and productivity of rice farming, and (b) to study whether there is a significant relationship between these psychological factors (work ethic, achievement motivation and innovative attitude) with farm productivity. Based on the analysis of descriptions of the main variables of the study, then through the method of "Likert's Summated Ratings" in the measurement of psychological variables in the know that the three psychological variables were in levels of "High" (from 5 measurement scales: from very low to very high). relatively variable work ethic scores 79.4 percent, 71.1 percent motivation, and innovative attitude of 78.4 percent.While for the variable productivity of rice varies from 1163.64 to 3030.30 kg / ha with an average of 2042.30 kg / ha of rice equivalent.In the method of Pearson correlation analysis then known that the variable work ethic and innovative attitude variables are very significant berhubingan with rice productivity, which in this case addressed by the magnitude of correlation coefficient (r = 0.67, p = 0.00) for variable ethos employment and productivity, and (r =0.696, p =0.00) for variable innovative attitude and productivity. this means that the size of the productivity of paddy rice farming posiyif no relationship with work ethic and innovative attitude of the farmers. while the motivation is not there a significant relationship with lowland rice farming productivity variable (r = 0.21, p =0.27). This means that farmers in increasing their business productivity is not driven by emotional intelligence but more driven olek because of necessity (there is no other choice) in developing rice farming. so that the size of the productivity is not determined by the high and low motivation of farmers.Keywords: Work ethic, achievement motivation, innovative attitude, farm productivity